Does Exposure to General Anesthesia Increase Risk of ADHD for Children Before Age of Three? - Song, Junjie; Li, Huifang; Wang, Ying; Niu, Chenguang (Frontiers in Psychiatry, 2021)
OBJECTIVE: To evaluate the relationship between frequency of exposure to general anesthesia before age of 3 and subsequent risk of diagnosis for Attention deficit hyperactivity disorder (ADHD). METHOD: We searched PubMed, Embase, Web of science and Cochrane Library database for eligible inclusion in the meta-analysis. The indicated outcomes were extracted from the included studies and the combined effects were calculated using RevMan software 5.3. RESULTS: Compared with no exposure to general anesthesia, single exposure to general anesthesia did not increase the risk of ADHD for children before the age of 3 (hazard ratio:1.14, 95%; confidence intervals: 0.97-1.35; P=0.11; I2=0%), while multiple exposures to general anesthesia did increase the risk of ADHD (hazard ratio:1.83; 95% confidence intervals:1.00–3.32; P=0.05; I2=81%). CONCLUSION: Multiple, but not single, exposures to general anesthesia in children before age of 3 increased the risk of ADHD.